Correlation between the microstructure and hydrogen embrittlement resistance in a precipitation-hardened martensitic stainless steel. (15th April 2021) - Yang, Zhe; Liu, Zhenbao; Liang, Jianxiong; Su, Jie; Yang, Zhiyong; Zhang, Boning; Sheng, Guangmin
Graphical abstract: Highlights: Hydrogen susceptibility of steel was reduced via high-temperature/long-term aging. Dissolution and transformation of η phase stabilized reversed austenite. Ripening of η phase relaxed stress concentration. Hydrogen-induced cracking was controlled by subcritical cracks. Abstract: Custom 465 precipitation-hardened stainless steel was subjected to various thermal treatments and then evaluated using tensile testing with a slow strain rate after electrochemical hydrogen charging. The investigation revealed that cryogenically-treated and thermally-aged (593 ℃) specimens exhibited superior resistance to hydrogen embrittlement. Prolonging the aging time reduced the hydrogen susceptibility, which was primarily attributed to the increased stability of reversed austenite caused by the dissolution and transformation of η-Ni3 Ti. Stress concentration relaxation due to the absence or ripening of η-Ni3 Ti further reduced the hydrogen susceptibility. Additionally, hydrogen-induced subcritical cracks initiated on the sample surface governed the fracture behavior.